A method to study antibiotic emission and fate for data-scarce rural catchments. (June 2019) - Chen, Qiuwen; Dong, Jianwei; Zhang, Tao; Yi, Qitao; Zhang, Jianyun; Hu, Liuming
Abstract: Estimations of antibiotic emission and fate and thereby ecological risk in rural catchments still lack feasible methods due to data scarcity. This study developed a new framework to evaluate the emission and fate of typical antibiotics for data-scarce catchments with uncertainty analysis. We estimated antibiotic discharge through questionnaire surveys; predicted antibiotic fate in air, water, soil, and sediment phases using a multimedia fugacity model; and analyzed the uncertainties of predicted environmental concentrations (PECs) and ecological risks of antibiotics. The developed method was tested in the Meijiang River catchment in China, and the uncertainty was systematically analyzed. Results showed that the discharge of tetracycline antibiotics (TCs) in the studied watershed was 8.56 t/a, with approximately 93% from veterinary medicine. TCs existed dominantly in the soil phase, accounting for 87.3% of total discharge. TC levels at the equilibrium states were the highest in sediment and soil, followed by water and air. The emission levels of TCs may cause slight risk to algae, daphniids, and fish in the receiving water based on the ecological risk evaluation of PECs. Despite of some uncertainties, the developed method provided an effective alternative to evaluate the ecological risks of antibiotics in catchments where sufficient monitored data are unavailable. Graphical abstract: Unlabelled Image Highlights: A systematic method was developed to study antibiotic risk in data-scarce catchment. The emission of antibiotic at catchment scale was studied by questionnaire inquiry. Fate of TCs was predicted by a multimedia fugacity model with acceptable accuracy. The developed method can determine the priority areas for antibiotic management. The method is broadly suitable to areas with intensive breeding and limited measurements.